Analisis Indeks Vegetasi dan Perancangan Sistem Monitoring Kawasan Ekowisata Mangrove Berbasis Hyper Spectral of Remote Sensing dan Design Thinking Framework - Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One of the challenges in decision-making for determining the direction of mangrove ecotourism development policies and programs on Tagalaya Island is the availability of mangrove databases at each observation station and remote sensing models used to identify mangrove forest density. This research offers the idea of combining the hyperspectral method of remote sensing with the information system design method design thinking framework. Meanwhile, the location of this research is the mangrove ecotourism area of Tagalaya Island, North Halmahera Regency, North Maluku Province, Indonesia. The findings of this study demonstrate the need to use remote sensing to locate and evaluate spatial data, particularly index values based on NDVI models for each Tagalaya Island observation station. The first and second observation stations are shown to be included in the unusual group by the computation results of the 2023 raster data in the mangrove area of Tagalaya Island. The third observation station is also included in the medium category. The monitoring information system for the Tagalaya mangrove ecotourism region is also a solution to the mangrove database challenge in deciding the direction of Tagalaya mangrove ecotourism policies and activities (SIMOKE Tagalaya). Thus, the problems and solutions encountered in enhancing the monitoring program of mangrove ecotourism areas on Tagalaya Island become relevant and contextual when applying the hyperspectral method of remote sensing and information system design using a design thinking framework.